An appraisal of the Laguna approach to community education - Avenido, Emilio A. 1904- ([Quezon City University of the Philippines], 1957)
This appraisal is a technique for community education and community improvement that was conceived and developed by schoolmen -- teachers, supervisors, and school administrators in the Division of Laguna during the latter part of the school year 1953-1954 and applied in all school communities since then. Its essential features, roadblocks or difficulties encountered in its application and improvement of the approach were determined in this study.
Bibliography: l. 106-108.
Thesis (M.Ed.)--University of the Philippines, 1957
Typewritten
Vita
Keywords: Community and school; Education -- Laguna